KEDUDUKAN KLAUSULA BAKU DALAM PROSES JUAL BELI ANTARA KONSUMEN DAN PELAKU USAHA PADA PERUSAHAAN PROPERTY PERUMAHAN (Fakultas Hukum Univesitas Kristen Indonesia Paulus, 2023)
In this country is on its way to Indonesian Gold 2045 experiencing many developments, especially in terms of buying and selling business. In society, where to live is very important. So many people want to buy a residential unit or housing unit. This study aims to determine the position of the standard clause in the process of buying and selling housing. The main problem in this thesis is the agreement that contains a clause that harms the consumer contained in the sale and purchase transaction which results in material loss by the consumer. This research method is using a normative juridical approach to literature. Normative juridical means research that refers to legal norms contained in laws and regulations and norms that apply in society or also concerning customs that apply in society. The technique of collecting data is by interviewing parties related to the application of standard clauses in the process of buying and selling residential properties, then law and consumer protection. The results of this study, namely the clauses that cause consumer losses in buying and selling housing are standard clauses that are prohibited in article 18 paragraph (1) because the standard clauses contained in buying and selling housing make consumers have no bargaining power during the buying and selling the process.